Identifying the Effective Factors on Neuropathic Diseases in Patients with Chronic pain Using Deep Neural Networks - Mobin Shaterian; Mohammad Teshnehlab (مدیریت مهندسی و رایانش نرم)
The main purpose of this research is finding major characteristics of clinical signs in the diagnosis of neuropathic disease in patients with chronic long-term pain. This type of disease is caused by various factors such as war, accidents and sports events. In this research, pain questionnaire of Shafa Neuroscience Research Center in Khatam-ol-Anbia Hospital in Tehran is study. By using the deep neural network and the nearest neighbor and the genetic algorithm and the auto encoder, the list of features was obtained with a precision measurement of 75 percentage. The McGill questionnaire was designated as the best effective feature for Neuropathic Pain.